Music festival motivation in China: free the mind. Issue 3 (3rd May 2016) - Li, Yan-Ning; Wood, Emma H.
Abstract : This paper explores the extent to which music festival attendance is 'universally' motivated or determined by the Chinese cultural and socio-political context. A novel qualitative approach was employed comprising observation of social media conversations and 'chat room' interviews with members of a festival online community. Seven motivators were identified, some similar to those in Western studies but others more specific to festival-goers in Mainland China. The culturally specific motivators were identified as 'spiritual escape' and 'spiritual pursuit' and the universal motivators as 'togetherness', 'love of the music', 'novel experience', 'music sharing' and 'educational enrichment'. This paper focuses on the two culturally embedded motivators only. The implications of the study are that, although, growing, there are still very few music festivals featuring 'pop' or 'western' style music and these few are relatively new to Chinese people. Their attendance at them is, therefore, motivated differently to attendees at similar festivals in western countries. These motivating factors are mediated by the particular social, political and cultural factors at work in this complex country. The findings indicate that although many of the motivational factors for attending a music festival appear to be universal, there are clearly factors which are culturally bound and therefore unique to the cultural context. These differences appear to be created by the social constraints, rapidly changing economy and the many contradictions inherent in modern Mainland China. These conditions create a greater contrast between everyday life in Mainland China and the liminal hedonistic space provided by the festival. Further research is needed to validate theses initial findings within China and to explore how rock music festival motivations differ in other non-western cultures.